Improving and humanizing animal models by microbiomic techniques - Hansen, Axel Kornerup (Henry Stewart Talks, 2015)
Bacteriological monitoring in lab rodents, Impact of the gut microbiota on rodent models, The interaction between the host and gut microbiota, The gut microbiota as a cause of variation in rodent models, Handle the impact: environmental & dietary fluctuations, Handle the impact: rodents with tailored-made gut microbiota
Archived at 2026/06/30